Revoking consent: A 'blind spot' in data protection law? - Curren, L; Kaye, J (2010)
The flow of personal data throughout the public and private sectors is central to the functioning of modern society. The processing of these data is, however, increasingly being viewed as a major concern, particularly in light of many recent high profile data losses. It is generally assumed that individuals have a right to withdraw, or revoke, their consent to the processing of their personal data by others; however this may not be straightforward in practice, or addressed adequately by the law. Examination of the creation of data protection legislation in Europe and the UK, and its relationship with human rights law, suggests that such a general right to withdraw consent was assumed to be inbuilt, despite the lack of express provisions in both the European Data Protection Directive and UK Data Protection Act. In this article we highlight potential shortcomings in the provisions that most closely relate to this right in the UK Act. These raise questions as to the extent of meaningful rights of revocation, and thus rights of informational privacy, afforded to individuals in a democratic society. © 2010 Xiaolu Zhang. Published by Elsevier Ltd. Allrights reserved.